“They Now Know That They Are Children of War”: Forcibly Abducted Mothers and Fathers Balancing Disclosure and Silencing to Their Children Born of War in Northern Uganda - De Nutte, Leen; De Haene, Lucia; Derluyn, Ilse (Frontiers in Political Science, 2022)
In recent years, scholars have emphasized the need for a relational understanding of the impact of collective violence pointing to the myriad interconnections between individual and communal experiences and consequences. These interconnections are particularly strong in the (re)integration of formerly abducted children and youth, and their children born of war, since various social, relational and cultural processes play a key role in their wellbeing and healing. One example is the way in which trauma communication is shaped by culture and context, and intersects at the level of the individual and the collective. In this paper, we will explore how forcibly abducted mothers and fathers in post-conflict Northern Uganda perceive the trauma communication about the context in which their children born in forced captivity were conceived. Case study research was used to understand the dynamic trajectories of this trauma communication, placing parents' experiences within broader life histories, and the social and relational context. Repeated interviews were performed with six mothers and four fathers who became parents in forced captivity with the Lord's Resistance Army (LRA). Central in the participants' stories is their agency in the careful, individual choice “to be silent” or “not to be silent” toward their children, family and community members. However, these choices are shaped—and often restricted—by the relational and cultural context. A dynamic interplay of several factors, such as the age of the child, the emotional impact of disclosure, a lack of resources and support in the upbringing of children, identity and belonging, and perceived or potential future stigmatization are explored in this paper. Trauma communication can be seen as a socially negotiated choice, interacting in a complex dialectic relationship between silencing, disclosing, forgetting and remembering. As such, the study revealed important insights into post-conflict healing and reintegration in the day-to-day lives of formerly abducted children and youth, and their children born of war, on an individual and collective level.